Exploring the Intersection of Education and Artificial Intelligence: A Comprehensive Review - Dash, Sagnika; Bhoi, Chandrasekhar (PT. Riset Press International, 2024)
The abstract commences by elucidating the foundational role of AI in reshaping traditional educational paradigms, emphasizing the advent of personalized learningexperiences tailored to individual student needs. Intelligent tutoring systems, driven by AI algorithms, are discussed for their ability to provide adaptive and customized support, fostering enhanced student engagement and performance. Educational analytics, powered by AI, is explored as a pivotal tool for extracting meaningful insights from vast datasets,informing evidence-based decision-making for educators and administrators.The review highlights notable case studies and successful implementations of AI in educational settingsacross various levels, from primary education to higher education and professional development. These case studies offer insights into the practical applications of AI, showcasing its effectiveness in optimizing teaching and learning outcomes.